2023
DOI: 10.7759/cureus.48198
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cervical Cancer in the Caribbean

Jamie Scott-Williams,
Amalia Hosein,
Patrick Akpaka
et al.

Abstract: Cervical cancer (CvC) is considered a preventable disease; however, in the Caribbean, it is still one of the fourth most common causes of death in women. Efforts to overcome obstacles to the treatment and control of this preventable disease are being made by several countries within the Caribbean. However, no health issue can be readily managed without first acquiring an understanding of the dynamics relating to its severity of impact reaching the target population, its clinical pathology, and the availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…The bivalent, quadrivalent, and 9-valent vaccines all prevent high-risk HPV 16 and 18, which were detected in 8 of 29 (28%) high-risk HPV-positive women in our study. Oncogenic HPV genotypes in Grenada that were uncommon in other Caribbean islands were HPV 53, our most frequent genotype, identified only in Cuba; HPV 56, noted by Scott-Williams et al ( 2 ) but not in our review of HPV in the Caribbean; and HPV 82, not previously reported. In Grenada, oncogenic genotypes HPV 35, 56, 69, 82 and probable oncogenic HPV 53 and 68 are not prevented by any current HPV vaccine.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…The bivalent, quadrivalent, and 9-valent vaccines all prevent high-risk HPV 16 and 18, which were detected in 8 of 29 (28%) high-risk HPV-positive women in our study. Oncogenic HPV genotypes in Grenada that were uncommon in other Caribbean islands were HPV 53, our most frequent genotype, identified only in Cuba; HPV 56, noted by Scott-Williams et al ( 2 ) but not in our review of HPV in the Caribbean; and HPV 82, not previously reported. In Grenada, oncogenic genotypes HPV 35, 56, 69, 82 and probable oncogenic HPV 53 and 68 are not prevented by any current HPV vaccine.…”
Section: Discussionmentioning
confidence: 42%
“…Caribbean countries have reported high-risk HPV genotypes that deviate from the HPV 16/18 predominance. A systematic review of the literature by Scott-Williams et al ( 2 ) on cervical cancer in the Caribbean from 1958 to 2022 states that “An exceptionally wide variation of HPV types exists within the Caribbean: HPV-16, 18, 33, 35, 42, 44, 45, 51, 52, 53, 55, 56, 58, 59, 66, 68, and 70.” This review notes the need for more research on cervical cancer in the Caribbean ( 2 ). Cancer in women is dominated by breast cancer in 159 countries and cervical cancer in 23 countries, with cervical cancer being the leading cause of death in 36 countries.…”
mentioning
confidence: 99%